THE NEWMAN PROCEDURE FOR ANALYZING STUDENTS' ERRORS IN SOLVING SYSTEMS OF LINEAR EQUATIONS - Veni Saputri; Rizal Kamsurya (KALAMATIKA Jurnal Pendidikan Matematika, 2021)
This study aimed to analyze students’ errors in problem-solving activities for systems of linear equations. The descriptive qualitative method was adopted and applied to obtain and process the research data. Research subjects were selected using the purposive sampling technique. Three participants were chosen according to their mathematical proficiency levels. Data collection was conducted by tests to measure students’ problem-solving abilities and semi-structural interviews to gather qualitative information about students’ errors in solving systems of linear equations. The interview results were analyzed using narrative analysis to obtain accurate conclusions. The study found that (1) low-ability students tend to perform error at the comprehension stage, (2) medium-ability students are likely to perform error at the transformation stage, and (3) high-ability students tend to perform error at the process skills stage. The solutions based on the ability level are: (1) low-ability students are required to read the question carefully, educators should emphasize the problem-solving procedure, and students should strengthen their understanding of the prerequisite learning content in problem-solving; (2) medium-ability students have to focus on the emphasis and development of their skills in understanding the language of a problem and balance with improving their understanding of learning content and contextual exercising; (3) high-ability students are provided with exercises that can improve their counting speed and accuracy of the subject in resolving a problem.